A Comparative Study on Pedagogy, Andragogy and Heutagogy in the Walk towards Education 5.0 - Nithiya N., Merlin Depsy (Celt: A Journal of Culture, English Language Teaching & Literature, 2023)
Learning influenced by multitasking and the development of rapid search technology, social networking, artificial intelligence, robotics, automation, and big data are considered to be the influences of the major shift from education 4.0 to education 5.0. Therefore, it becomes important for teachers and students to understand the theoretical gaps that exist in Pedagogy, Andragogy, and Heutagogy in order to spearhead a broader discussion about how the teaching-learning process occurs in and will happen in the post new normal. This paper is an attempt to compare and suggest ways to integrate Pedagogy, Andragogy, and Heutagogy in New Indian English Classrooms where connectivity is key to its success.